IDENTIFIKASI STRUKTUR BAWAH PERMUKAAN BERDASARKAN DATA ANOMALI GRAVITASI DI PULAU LOMBOK - Imelda Threza; Winardi Tjahyo Baskoro; Ida Bagus Alit Pramarta; I Ketut Sukarasa; Putu Suardana; I Wayan Supardi (Kappa Journal, 2024)
Abstract: Research on the identification of subsurface structures based on gravity anomaly data on Lombok Island. This research aims to create a map and determine the value of the complete Bouguer anomaly, regional anomaly, residual anomaly, subsurface density value and create a 2-D model of the subsurface structure. The data used is secondary data, namely satellite gravity anomaly data obtained from the topex website. Data processing in this research uses the gravity method. In this method, gravity correction will be carried out, making a complete bouguer anomaly map, conducting spectrum analysis, separating regional and residual anomalies using butterworth filters and forward modeling to obtain a 2-D model of the subsurface structure. The results of the complete bouger anomaly map are 10.2 to 297.1 mGal, regional anomalies 18.0 to 271.1 mGal and residual anomalies between (-52.9 to 32.4) mGal. The results of forward modeling show that the subsurface geological structure on Lombok Island has a density range between 1 to 2.9 g/cm3, so that from the range of rock density values it can be estimated that the subsurface structure of Lombok Island is divided into East Lombok consisting of Soil rocks (1 to 1.99 g/cm3), Lime Stone (2 to 2, 27 g/cm3), Andesite (2.4 to 2.63 g/cm3) and Basalt (2.71 to 2.99 g/cm3), for West Lombok consists of Lime Stone (2.08 to 2.6 g/cm3), Andesite (2, 68 to 2.77 g/cm3) and Basalt (2.85 to 2.99 g/cm3) and for Central Lombok consists of Andesite (2.41 to 2.72 g/cm3), Basalt (2.84 to 2.99 g/cm3).